The Notion of Absurdity in Albert Camus's "The Myth of Sisyphus" - Avagyan, Naira; Zakalashvili, Ita (Bulletin of Yerevan University B: Philology, 2025)
The present research is an attempt to analyze "The Myth of Sisyphus" by Albert Camus on the stylistic and literary levels, giving a general notion about Camus' approach to absurdity. The original book is in French but the translation is too close both in style and vocabulary, consequently making it possible to be a subject of analysis. First Camus explains what absurd means, how a person obtains it, and then represents some ways out of absurdity, which are suicide and leap of faith. The author rejects both of the attempts of making life meaningful, thus, giving his own solution to the problem, which is recognition. For Camus, the meaningful life lies in recognizing the following: life itself is meaningless and you are the one who can make it meaningful. At the end of the work Camus puts his theory into practice by representing Sisyphus, an absurd hero, who is the main character of the book.
Keywords: absurd; suicide; philosophy; solution; faith; hope; existence